Efektivitas Sistem Pengaduan dan Informasi (Siaduin) Pada Kantor Imigrasi Kelas I Non TPI Depok - Rafif Nadhif Muflih; Mawar Mawar (Jurnal Media Administrasi, 2024)
The SIADUIN application system provides a number of services, namely complaints for facilities and infrastructure, services to complaints against foreigners and there is also an information service about services available at the Class I Non TPI Depok Immigration Office. However, in its implementation, various problems were found, one of which was that the results of complaints and complaints from the public were still slow in capturing and responding to them and they also often complained about a slow system and the absence of Playstore and Appstore, which made it easier for the public to access them. This research aims to determine and analyze the effectiveness of the SIADUIN application system and improve the quality of public services by the Class I Non TPI Depok Immigration Office. To determine the effectiveness of the SIADUIN application using the program effectiveness theory proposed by Budiani (2007; 53), there are four indicators to determine program effectiveness, namely, accuracy of program targets, program socialization, program objectives and program monitoring and supervision. The research method used in this research is a descriptive method with a qualitative approach. The results of this research show that the effectiveness of the SIADUIN application system in improving the quality of complaints and public services by the Class I Non TPI Depok Immigration Office in complaint and information services is still not effective. It is known that the recording and management of complaints is recapped every two months, this is inversely proportional to the complaints and grievances submitted by the public every day.